Primary Localized Cutaneous Nodular Amyloidosis Presenting as Milia: An Unusual Clinical Manifestation - Wang Y; Zhou H; Wang J; Wang P (Dove Medical Press, 2022)
Yanqing Wang,1 Hongyu Zhou,1 Jiaqi Wang,1 Ping Wang2 1Department of Dermatology, Hangzhou Third People's Hospital, Zhejiang Chinese Medical University, Hangzhou, 310009, People's Republic of China; 2Department of Dermatology, Hangzhou Third People's Hospital, Affiliated Hangzhou Dermatology Hospital of Zhejiang University School of Medicine, Hangzhou, 310009, People's Republic of ChinaCorrespondence: Ping Wang, Department of Dermatology, Hangzhou Third People's Hospital; Affiliated Hangzhou Dermatology Hospital, Zhejiang University School of Medicine, Westlake Ave 38, Hangzhou, 310009, People's Republic of China, Tel +8613588812862, Email dermwang@aliyun.comAbstract: Primary localized cutaneous nodular amyloidosis (PLCNA) is rare and clinically noncharacteristic, presenting mostly as plaque-like lesions. We report a case of a progressively larger erythematous plaque following a contusion of the skin on the right zygomatic area, which was strangely covered with recurrent scattered 2 mm whiteish blisters to the extent that it was misdiagnosed as a herpesvirus infection several times over a decade. Pathology and special staining diagnosed nodular amyloidosis with milia.Keywords: primary localized cutaneous nodular amyloidosis, milia, local trauma, plaque